Determinants of Students' Consumptive Behavior: Evidence from Sharia Financial Literacy, Financial Behavior, Peer Pressure, and Fintech Payment in Yogyakarta - Ratna Sofiana; Najwa Airin; Satria Utama (SHAHIH: Journal of Islamicate Multidisciplinary, 2026)
This study aims to examine the influence of Sharia Financial Literacy, Financial Behavior, Peer Pressure, and Financial Technology Payments on Consumptive Behavior among students in the Special Region of Yogyakarta. The increasing adoption of digital payment systems and changing consumption patterns among university students make this topic particularly relevant. This research employs a quantitative approach using a purposive sampling technique to select respondents who meet the specified criteria. Data were collected from 150 student respondents across the Special Region of Yogyakarta and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS 3.0 software. The findings indicate that Financial Behavior, Peer Pressure, and Financial Technology Payments each have a significant positive effect on students' Consumptive Behavior. In contrast, Sharia Financial Literacy has a negative but statistically insignificant effect on Consumptive Behavior. These results suggest that social influence, financial habits, and the use of digital payment technology play a more dominant role in shaping students' consumptive behavior than their level of Sharia financial literacy.